2021
DOI: 10.3389/fgene.2021.780431
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Long Non-Coding RNAs AC010082.1 and AC011443.1 as Biomarkers of Coronary Heart Disease Based on Logistic Stepwise Regression Prediction Model

Abstract: Coronary heart disease (CHD) is a global health concern with high morbidity and mortality rates. This study aimed to identify the possible long non-coding RNA (lncRNA) biomarkers of CHD. The lncRNA- and mRNA-related data of patients with CHD were downloaded from the Gene Expression Omnibus database (GSE113079). The limma package was used to identify differentially expressed lncRNAs and mRNAs (DElncRNAs and DEmRNAs, respectively). Then, miRcode, TargetScan, miRDB, and miRTarBase databases were used to form the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Xu et al found that eight epithelial-mesenchymal transition-related lncRNAs are potential biomarkers in CAD ( 42 ). Liu et al found that AC010082.1 and AC011443.1 could be biomarkers of CAD based on the ceRNA mechanism and logistic stepwise regression prediction model, and they validated that these lncRNAs were upregulated in CADs using RT-PCR ( 43 ). In this study, we also uncovered two new lncRNAs (AL359237.1 and LINC01480) by mining the GSE113079 dataset, which might predict the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al found that eight epithelial-mesenchymal transition-related lncRNAs are potential biomarkers in CAD ( 42 ). Liu et al found that AC010082.1 and AC011443.1 could be biomarkers of CAD based on the ceRNA mechanism and logistic stepwise regression prediction model, and they validated that these lncRNAs were upregulated in CADs using RT-PCR ( 43 ). In this study, we also uncovered two new lncRNAs (AL359237.1 and LINC01480) by mining the GSE113079 dataset, which might predict the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of epidemiological studies have reported a link between chronic kidney disease (CKD) and CHD, perhaps providing another perspective on clinical treatment. Traditional Chinese Medicine (TCM) has been widely used in treating CHD for a long time and studies have confirmed the biological mechanism ( 3 , 4 ). With the change of social lifestyle, the TCM syndrome for unstable angina pectoris with coronary heart disease presents a combination form of “kidney deficiency and blood stasis.” A clinical epidemiological survey on the distribution of TCM syndromes showed that qi deficiency was the main symptom of angina pectoris in coronary heart disease, accounting for up to 78.8%, second only to blood stasis, of which heart and kidney qi deficiency was the mainstay ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of epidemiological studies have reported a link between chronic kidney disease (CKD) and CHD, perhaps providing another perspective on clinical treatment. Traditional Chinese Medicine (TCM) has been widely used in treating CHD for a long time and studies have confirmed the biological mechanism (3,4). With the change of social lifestyle, the TCM syndrome for unstable angina pectoris with coronary heart disease presents a combination form of "kidney deficiency and blood stasis."…”
mentioning
confidence: 99%